IOU seasonal report, spring 1999, Fred Lesher - Lesher, Fredet al (1999)
An annotated list of birds sighted by Fred Lesher. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1999. Epson - sheet feed/flatbed